2015
DOI: 10.5032/jae.2015.01155
|View full text |Cite
|
Sign up to set email alerts
|

The Cultural Adaptation Process During a Short-term Study Abroad Experience in Swaziland

Abstract: Globalization continuously shapes our world and influences post-secondary education. This study explored the cultural adaptation process of participants during a short-term study abroad program. Participants experienced stages which included initial feelings, cultural uncertainty, cultural barriers, cultural negativity, academic and career growth, feelings throughout the program, and cultural growth. The findings from this study should be used to design and implement short-term study abroad programs that infus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…We conclude, therefore, that these experiences profoundly influenced shifts in students' perspectives. In the agricultural education literature, Conner and Roberts (2015) noted that cultural forces often emerge during study abroad courses; however, they explained that such aspects ". .…”
Section: Discussionmentioning
confidence: 99%
“…We conclude, therefore, that these experiences profoundly influenced shifts in students' perspectives. In the agricultural education literature, Conner and Roberts (2015) noted that cultural forces often emerge during study abroad courses; however, they explained that such aspects ". .…”
Section: Discussionmentioning
confidence: 99%
“…The models provided direction to this study by giving insight on how an individual feel's when communicating with people from other cultures. The combined use of the models sets the stage for cultural adaptation investigation specifically in short-term study abroad programs and has been previously used in a research study by Conner and Roberts (2015). The U-curve of culture shock depicted in Figure 1.…”
Section: Theoretical/conceptual/operationalmentioning
confidence: 99%
“…Recent calls to provide more educational opportunities abroad are supported by an extensive body of academic literature, in which myriad student benefits have been documented. In particular, the primary reported outcomes for students who studied abroad include: (a) enhanced cultural competence; (b) a more developed global perspective; (c) deeper understanding of international issues; (d) increased abilities to communicate and collaborate with diverse groups; (e) the development of international networks beneficial to students' future careers; and (f) increased self-efficacy and self-confidence when working in unfamiliar situations Conner, Milius, Stripling, Loizzo, & Doerr, 2019;Conner & Roberts, 2015;Foster, Sankey Rice, Foster, & Barrick, 2014;Hainline et al, 2018;. Students who participated in a study abroad course in college were also found to be more likely to continue to engage in intercultural activities in the future than students who had not participated (Murphey, Sahakyan, Yong-Yi, & Magnan, 2014).…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%
“…Colleges of agriculture have, therefore, been tasked with producing globally minded and skilled professionals (National Association of State and Land-Grant Colleges [NASULGC], 2004). In response, recent literature has primarily focused on identifying the best practices for creating effective study abroad courses in agriculture Conner et al, 2019;Conner & Roberts, 2015;Fabregas-Janeiro, Kelsey, & Robinson, 2011;Pigg, Richardson, Roberts, & Stair, in press;. However, well-designed programs may provide little value if university agriculture students continue to choose not to enroll.…”
Section: Introduction and Review Of Literaturementioning
confidence: 99%